2019
DOI: 10.1111/cdev.13229
|View full text |Cite
|
Sign up to set email alerts
|

Taxometric Analysis of Secure Base Script Knowledge in Middle Childhood Reveals Categorical Latent Structure

Abstract: Taxometric investigation of scripted attachment representations in lateadolescence and adulthood suggests that variations in secure base script knowledge consist of differences in degree (dimensional latent structure) rather than differences in kind (categorical latent structure). However, the latent structure of secure base script knowledge in younger cohorts has gone unexplored. This study presents a downward extension of prior taxometric work using the middle childhood version of the Attachment Script Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 37 publications
5
18
1
Order By: Relevance
“…Studies in the last few years have reported evidence of a generalized secure base script in both adolescent and adult samples (Waters et al, ) and even in some findings from late middle childhood (Boldt, Waters, & Kochanska, ; Waters et al, ), supporting our interpretation that script knowledge tends to be broad based. Confirmatory factor analyses indicated an underlying latent generalized script knowledge that encompassed a range of attachment narratives included in the different age‐appropriate ASAs.…”
Section: Discussionsupporting
confidence: 87%
“…Studies in the last few years have reported evidence of a generalized secure base script in both adolescent and adult samples (Waters et al, ) and even in some findings from late middle childhood (Boldt, Waters, & Kochanska, ; Waters et al, ), supporting our interpretation that script knowledge tends to be broad based. Confirmatory factor analyses indicated an underlying latent generalized script knowledge that encompassed a range of attachment narratives included in the different age‐appropriate ASAs.…”
Section: Discussionsupporting
confidence: 87%
“…showed that links between attachment and prosocial behavior are hard to nd in middle childhood, but become more apparent in adolescence [64]. This is in line with research showing that SBS knowledge is still signi cantly developing in middle childhood [22]. It could be that, at ages when the SBS further matured, links with prosocial behavior are more easily found.…”
Section: Discussionsupporting
confidence: 79%
“…Age was positively correlated with SBS knowledge. This suggests that, with increasing age, children displayed more SBS knowledge, which is expected based on previous SBS research in middle childhood [19]. In addition, perceptual intelligence was positively correlated with SBS knowledge suggesting that part of the variance in our measure of SBS knowledge related to intelligence.…”
Section: Preliminary Analysessupporting
confidence: 75%
“…Firstly, this could have been caused by our measure of SBS knowledge, which was novel and used for the rst time in the current study. Our measure diverged from the much better studied word-prompt SBS measure where children are asked to use a list of words that roughly suggest a secure base story in order to create narratives that can be coded for SBS knowledge [56,57,19]. However, when developing the current study, we were worried that this narrative approach was going to be too di cult given ADS children's expected limited cognitive and narrative skills [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation